Controlled release of doxorubicin from thermosensitive poly(organophosphazene) hydrogels - Kang, Gyung D.; Cheon, Se H.; Song, Soo-Chang (ELSEVIER, 2006)
Thermosensitive poly(organophosphazenes) bearing hydrophobic isoleucine ethyl esters group and hydrophilic alpha-amino-omega-methoxypoly(ethylene glycol) of the molecular weight 550 along with hydrolysis-sensitive glycyl lactate ethyl esters have been synthesized for sustained delivery of anticancer drug. The aqueous solution of polytorganophosphazenes) containing doxorubicin, that represents chemotherapeutic agent for cancer treatment, was transformed into hydrogel with good gel strength at body temperature via hydrophobic interactions. Solubility of hydrophobic doxorubicin in the aqueous poly(organophosphazene) solution was dramatically improved as compared with that in PBS (0.01 M, pH 7.4). The hydrogel property of poly (organophosphazenes) was affected on incorporation of doxorubicin, resulting in increase of gelation temperature and decrease of gel strength. The release of loaded doxorubicin from the polymer hydrogel was significantly sustained over 20 days and the effect of get strength, polymer concentration and drug concentration on the release rate were observed. The release of doxorubicin from the polymer gels was effectively controlled by the gel strength. As a result of investigating anticancer efficacy using cancer cell line of mouse lymphoblast of P388D1, the efficacy of doxorubicin was observed to be constant over a prolonged period of times for more than 30 days, indicating that the release of doxorubicin was sustained for a long time without any initial burst release, and that the delivery system was an excellent candidate for locally injectable gel-depot system. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: BIODEGRADABLE BLOCK-COPOLYMERS; PEG-GRAFTED CHITOSAN; THERMOREVERSIBLE GELATION; DELIVERY; DRUG; PROTEINS